Victimization of psychiatric patients - Ćirić Zoran (Temida)
Because of their biological, and, especially, psychological and social characteristics, psychiatric patients can often become victims of very different modalities of activities which cause harm to them. These factors exist and have origin in social context where mentally ill live, but they can be factors that belong to whole social community as well. The aim of this paper is to review factors which contribute to victimisation of psychiatric patients, to point out a risk of their victimisation and their specific predispositions, as well as negative social circumstances which make psychiatric patients vulnerable to become victims in broader sense. In addition, the proposal of possible typology of psychiatric patients as victims is included as well.